How can health technology assessment support our response to public health emergencies? - Aparna Ananthakrishnan; Alia Cynthia Gonzales Luz; Sarin KC; Leslie Ong; Cecilia Oh; Wanrudee Isaranuwatchai; Saudamini Vishwanath Dabak; Yot Teerawattananon; Hugo C. Turner (BMC, 2022)
Abstract Public health emergencies (PHEs), such as the COVID-19 crisis, are threats to global health and public order. We recommend that countries bolster their PHE responses by investing in health technology assessment (HTA), defined as a systematic process of gathering pertinent information on and evaluating health technologies from a medical, economic, social and ethical standpoint. We present examples of how HTA organizations in low- and middle-income countries have adapted to supporting PHE-related decisions during COVID-19 and describe the ways HTA can help the response to a PHE. In turn, we advocate for HTA capacity to be further developed globally and for increased institutional acceptance of these methods as a building block for preparedness and response to future PHEs. Finally, the long-term potential of HTA in strengthening health systems and embedding confidence and transparency into scientific policy should be recognized.